Strategi Pengembangan Wisata Air Terjun di Kabupaten Bogor, Jawa Barat - Kristiana, Yustisia; Wea, Maria Irma Jasintha; Salimin, Vedelieni (LPPM Institut Pendidikan Nusantara Global, 2024)
Waterfall tourism is a natural tourist attraction that is an option when traveling to Bogor Regency. The purpose of this research is to identify the potential for waterfall tourism in Bogor Regency and the strategy for developing waterfall tourism to become a leading tourist attraction in Bogor Regency. The research method used is a qualitative approach. The informants selected by purposive sampling technique were tourism stakeholders included in the keyperson, namely the Bogor Regency Tourism Office, managers of waterfall tourist attractions, tourists, business owners, and the local community. The data analysis technique used in this study is interactive analysis. For the selection of alternative development strategies, a SWOT analysis is carried out. The results of the study show that the tourism potential of waterfalls in Bogor Regency has an attractiveness and uniqueness which is its strength. Based on the Internal Factor Analysis Strategy (IFAS) the main strength aspect is community participation in managing waterfall tourism and the biggest weakness is accessibility to waterfall tourism which is still difficult. Meanwhile, based on the External Factor Analysis Strategy (EFAS), the biggest opportunity aspect is tourists who help promote waterfall tourism and the biggest threat is natural disasters. The results of the SWOT analysis show that in developing waterfall tourism in Bogor Regency, a defensive strategy can be applied.